Pharmacology : examination & board review. - Trevor, Anthony J. 4 0 16; Katzung, Bertram G.;Kruidering-Hall, Marieke.;Masters, Susan B.; 5 (New York : McGraw-Hill Medical, 2013)
Delivers a clear, concise review of fundamental concepts backed by more than 1,000 review questions and answers.
Basic principles -- Autonomic drugs -- Cardiovascular drugs -- Drugs with important actions on smooth muscle -- Drugs that act in the central nervous system -- Drugs with important actions on blood, inflammation, & gout -- Endocrine drugs -- Chemotherapeutic drugs -- Toxicology -- Special topics.
Previous ed.: 2010.;A Lange medical book.
Includes bibliographical references (p. 579) and index.
Keywords: 2 -- 0; 6; Examinations -- Pharmacology;Pharmacology;Pharmacology -- 20 -- Study guides.;Examination Questions.;Outlines.; 20; 2